Self Efficacy and Job Satisfaction : The Mediating Role Of Work Design - Amrullah, M; Trinanda, Okki (Human Resource Management Studies, 2023)
This study analyzes (1) the effect of self efficacy on job satisfaction in the employee at Department of Maritime Affairs and Fisheries of West Sumatra Province (2) the effect of self efficacy on work design for employee at Department of Maritime Affairs and Fisheries of West Sumatra Province (3) the effect of work design on job satisfaction of employee at Department of Maritime Affairs and Fisheries of West Sumatra Province (4) the effect of self efficacy on job satisfaction through work design for employee at Department of Maritime Affairs and Fisheries of West Sumatra Province. This research is a causal research. The population in this study were employee at the Department of Maritime Affairs and Fisheries of West Sumatra Province. The number of samples used is the population of 92 people who are taken using total sampling. Collecting data using a questionnaire with a Likert scale. The analysis technique used is SEM using Smart PLS analysis. The results of this study show: (1) Self Efficacy is significant to job satisfaction. (2) Self efficacy is significant for work design for employee at Department of Maritime Affairs and Fisheries of West Sumatra Province (3) Work design is significant for job satisfaction for Department of Maritime Affairs and Fisheries of West Sumatra Province (4) Self efficacy is significant for job satisfaction being through work design to the employee at Department of Maritime Affairs and Fisheries of West Sumatra Province.